Comparative analysis of multi-criteria decision making methods for the assessment of optimal SVC location - AYDIN, FARUK (My University, 2022)
The goal of multi-criteria decision making (MCDM) is to select the most appropriate of the alternatives by evaluating many conflicting criteria together. MCDM methods are widely available in the literature and have been used in various energy problems. The key problems studied in electrical power systems in recent years have included voltage instability and voltage collapse. Different flexible alternating current transmission systems (FACTS) equipment has been used for this purpose for decades, increasing voltage stability while enhancing system efficiency, reliability and quality of supply, and offering environmental benefits. Finding the best locations for these devices in terms of voltage stability in actual electrical networks poses a serious problem. Many criteria should be considered when determining the most suitable location for the controller. The aim of this paper is to provide a comparative analysis of MCDM techniques to be used for optimal location of a static VAR compensator (SVC) device in terms of voltage stability. The ideal location can be determined by means of sorting according to priority criteria. The proposed approach was carried out using the Power System Analysis Toolbox (PSAT) in MATLAB in the IEEE 14-bus test system. Using ten different MCDM methods, the most appropriate locations were compared among themselves and a single ranking list was obtained, integrated with the Borda count method, which is a data fusion technique. The application results showed that the methods used are consistent among themselves. It was revealed that the integrated model was an appropriate method that could be used for optimal location selection, providing reliable and satisfactory results to power system planners.
Keywords: Elektrik-Elektronik Mühendisliği; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences; Borda count method; FACTS; MCDM; optimal location; PSAT; voltage stability